P 100 A 64-channel dry multipin-electrode cap for EEG. Issue 10 (October 2017) - Haueisen, J.; Fiedler, P.; Zanow, F.; Fonseca, C.
Abstract : Multichannel Electroencephalography (EEG) is widely used in clinical neurology and neuroscientific research. EEG caps with 64 wet Silver/Silver-Chloride (Ag/AgCl) electrodes represent an often-used standard in the field. Reproducible electrode-skin contact for these electrodes is ensured by electrolyte gel or paste. Thus, these electrodes require specific mechanisms to apply and hold the gel at the electrode positions in the caps and require skilled personnel to apply the EEG cap. Dry electrodes allow more degrees of freedom in the design and fabrication of EEG caps and can be self-applied without preparation. We present a novel 64-channel EEG cap with dry electrodes. The base material of the EEG cap is a light-weight and flexible fabric, which contains small holes (perforation) making it breathable. Polyurethane (PU) based multipin electrodes serve as dry contact electrodes. A coating provides electrical conductivity of these polymer based electrodes. The use of silver coating opens the way for dry AgCl electrodes and thus, signal quality similar to wet Ag/AgCl electrodes. Thin coaxial wires are soldered to the bottom of the electrodes enabling active shielding. A second layer of fabrics protects the electrodes and the wires. Our results demonstrate that resting state EEG, eye movements, alpha activity, and pattern reversal VEP can be recorded with the novel dry 64-channel EEG cap with short preparation time and without significant differences between the novel EEG cap and a conventional cap based on wet Ag/AgCl electrodes. In conclusion, the proposed novel 64-channel EEG cap with dry electrodes can potentially replace conventional wet 64-channel EEG caps and thus enable new fields of application like brain-computer-interfaces and mobile EEG acquisition.